2017
DOI: 10.1111/dgd.12351
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endocannabinoid system in vertebrates: Emphasis on the zebrafish model

Abstract: The endocannabinoid system (eCBs), named after the plant Cannabis sativa, comprises cannabinoid receptors, endogenous ligands known as “endocannabinoids”, and enzymes involved in the biosynthesis and degradation of these ligands, as well as putative transporters for these ligands. ECBs proteins and small molecules have been detected in early embryonic stages of many vertebrate models. As a result, cannabinoid receptors and endogenous as well as exogenous cannabinoids influence development and behavior in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 95 publications
(200 reference statements)
3
87
0
2
Order By: Relevance
“…Previous findings point to a role of the eCB system in zebrafish development (Akhtar et al, 2013(Akhtar et al, , 2016Carty et al, 2017;Oltrabella et al, 2017;Watson et al, 2008). For instance, reduced gene expression for the CB 1 R results in a number of deficits in axonal growth, neuronal branching and fasciculation of hindbrain neurons that are known to express the CB 1 R (Watson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings point to a role of the eCB system in zebrafish development (Akhtar et al, 2013(Akhtar et al, , 2016Carty et al, 2017;Oltrabella et al, 2017;Watson et al, 2008). For instance, reduced gene expression for the CB 1 R results in a number of deficits in axonal growth, neuronal branching and fasciculation of hindbrain neurons that are known to express the CB 1 R (Watson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Within the central nervous system (CNS), CB 1 Rs are highly expressed in regions of the basal ganglia such as the substantia nigra pars reticulata and globus pallidus, as well as in the hippocampus and cerebellum (Herkenham et al, 1990). CB 1 Rs appear to be localized to presynaptic regions, where they play neuromodulatory roles and have been implicated in homeostasis (Oltrabella et al, 2017;Ruginsk et al, 2015). CB 2 Rs were first thought to be located outside of the CNS, associated with the immune system, the reproductive system and the digestive system (Howlett and Abood, 2017;Mouslech and Valla, 2009), but recent findings point to a clear distribution within the CNS of various organisms (Jordan and Xi, 2019;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The CB1 cannabinoid receptor-interacting protein 1 (CNRIP1), for example, is a protein involved in synaptic plasticity and modulates neurotransmission (Howlett et al, 2010) and was differentially expressed in the offspring of parents that were behaviourally sensitive to elevated CO2. Previous studies on zebrafish revealed that CNRIP1 is highly expressed in the nervous system, particularly in developing fish, and CNRIP1 interacts with the cannabinoid receptor 1, a receptor critical for the functional development of vision and locomotion (Fin et al, 2017;Oltrabella et al, 2017). In the offspring of tolerant parents, we further found differentially expressed proteins, such as the vascular cell adhesion protein (VCAM-1), to be involved in cellular process and organ development (Kong et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Oltrabella et al . () review roles of the endocannabinoid system (eCBs) in synaptic transmission, behaviors, and development in mammals, amphibians and zebrafish, and discuss evolutionary considerations. Takeuchi et al .…”
mentioning
confidence: 99%
“…Yamamoto et al (2017b) review descending pathways to the spinal cord in teleosts, which play crucial roles in controlling locomotion, including the rubospinal tract which originates from the nucleus ruber identified recently, and compare them with the descending pathways in mammals. Oltrabella et al (2017) review roles of the endocannabinoid system (eCBs) in synaptic transmission, behaviors, and development in mammals, amphibians and zebrafish, and discuss evolutionary considerations. Takeuchi et al (2017) review matingrelated behaviors in the medaka fish, namely female mating preference and male mate-guarding behavior, and their control by neuropeptide neuromodulatory systems.…”
mentioning
confidence: 99%